Marketing and designing the tourist experience - Frochot, Isabelle; Batat, Wided (Oxford : Goodfellow Publishers Limited, 2013)
The topic of 'experience' is becoming central to full understanding of consumer behaviour. This book covers the key sectors where it is critical - from resort management and tourist information to destination marketing. International in scope it backs up the theory throughout with relevant case materials, questions and exercises.
Includes bibliographical references and index.
Keywords: Tourism -- Management; Tourism -- Marketing; Place marketing